Photomodulated reflectance study on optical property of InN thin films grown by reactive gas-timing rf magnetron sputtering - Porntheeraphat, S.; Nukeaw, J. (My University, 2008)
The photoreflectance (PR) spectroscopy has been applied to investigate the band-gap energy (E g ) of indium nitride (InN) thin films grown by rf magnetron sputtering. A novel reactive gas-timing technique applied for the sputtering process has been successfully employed to grow InN thin films without neither substrate heating nor post annealing. The X-ray diffraction (XRD) patterns exhibit strong peaks in the orientation along (0 0 2) and (1 0 1) planes, corresponding to the polycrystalline hexagonal-InN structure. The band-gap transition energy of InN was determined by fitting the PR spectra to a theoretical line shape. The PR results show the band-gap energy at 1.18 eV for hexagonal-InN thin films deposited at the rf powers of 100 and 200 W. The high rf sputtering powers in combination with the gas-timing technique should lead to a high concentration of highly excited nitrogen ions in the plasma, which enables the formation of InN without substrate heating. Auger electron spectroscopy (AES) measurements further reveal traces of oxygen in these InN films. This should explain the elevated band-gap energy, in reference to the band-gap value of 0.7 eV for pristine InN films. © 2008 Elsevier B.V. All rights reserved.
Keywords: InN; Photoreflectance spectroscopy; Reactive gas-timing; rf Sputtering